2011
DOI: 10.1063/1.3615123
|View full text |Cite
|
Sign up to set email alerts
|

Observing peculiar γ-ray pulsars with AGILE

Abstract: The AGILE γ-ray satellite provides large sky exposure levels (≥10 9 cm 2 s per year on the Galactic Plane) with sensitivity peaking at E ∼100 MeV where the bulk of pulsar energy output is typically released. Its ∼1 µs absolute time tagging capability makes it perfectly suited for the study of γ-ray pulsars. AGILE collected a large number of γ-ray photons from EGRET pulsars (≥40,000 pulsed counts for Vela) in two years of observations unveiling new interesting features at sub-millisecond level in the pulsars' h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…In the context of a systematic monitoring of the high-energy activity of FRB 180916.J0158+65, our observations help constrain the rate of possible GFs with a unique broad-band sensitivity from 1 to 100 keV, with upper limits on the released energy of possible bursts of E 10 46 erg or even less for durations, ∆ t 0.1 s. Considering the different energy bands, these values are comparable with those obtained in the X-rays with Chandra and XMM-Newton (Scholz et al 2020;Pilia et al 2020) and they are significantly more sensitive than those obtained with all-sky monitors such as Fermi/GBM (Scholz et al 2020). Under the assumption that the frequency of radio bursts of FRB 180916.J0158+65 around peak is the same for all periods, our observations almost certainly cover one or more of them.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In the context of a systematic monitoring of the high-energy activity of FRB 180916.J0158+65, our observations help constrain the rate of possible GFs with a unique broad-band sensitivity from 1 to 100 keV, with upper limits on the released energy of possible bursts of E 10 46 erg or even less for durations, ∆ t 0.1 s. Considering the different energy bands, these values are comparable with those obtained in the X-rays with Chandra and XMM-Newton (Scholz et al 2020;Pilia et al 2020) and they are significantly more sensitive than those obtained with all-sky monitors such as Fermi/GBM (Scholz et al 2020). Under the assumption that the frequency of radio bursts of FRB 180916.J0158+65 around peak is the same for all periods, our observations almost certainly cover one or more of them.…”
Section: Discussionsupporting
confidence: 78%
“…Although no radio burst has been reported to date during the Insight-HXMT observing window, it is worth estimating the probability that FRB 180916.J0158+65 gave no FRBs. Ignoring the complex dependence on frequency (CHIME/FRB Collaboration 2020b; Pilia et al 2020;Chawla et al 2020), here we focus on the homogeneous sample detected with CHIME. Considering the ±0.9 d interval centred on the peak of radio activity, which has a burst rate of 1.8 +1.3 −0.8 h −1 (CHIME/FRB Collaboration 2020b), the net exposure of Insight-HXMT is ∼8.5 h. The probability of no FRBs over the duration of the Insight-HXMT observation is 2 × 10 −4 at most.…”
Section: Detection Of Radio Bursts During Insight-hxmt Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we assume a homogeneous population of FRB sources, which may not be the case, and it is also possible that some (e.g., soft X-ray, or blue optical) FRB counterparts are absorbed or scattered in dense surrounding media. Multiwavelength observations of nearby individual sources (e.g., Casentini et al 2020;Pilia et al 2020;Tavani et al 2020) are a complementary means to address the nature of the FRB engine and emission mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…PSR B1509 is unique among the known γ -ray spin-down powered pulsars for its very soft γ -ray spectrum and a very strong surface magnetic field. It is suggested that there may be a new class of spin-down powered pulsar with high magnetic field (>10 13 G) and soft γ -ray radiation, called soft γ -ray pulsar (Pilia & Pellizzoni 2011). Also, there is at least another pulsar that is similar to PSR B1509, PSR J1846−0258, a young pulsar with P ∼ 324 ms and surface magnetic field B s ∼ 4.9 × 10 13 G, which cannot be detected by Fermi but is seen by X-ray telescopes (Kuiper & Hermsen 2009;Parent et al 2011).…”
Section: Introductionmentioning
confidence: 99%